The Binding Force of International Legal Standards in the Face of the Recurrent Practice of Soft Law - Boubacar Sidi, Diallo (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
Soft law facilitates cooperation between international actors. Already, the elaboration of international law is a matter of shared competence between States, traditionally recognized as the only subjects of international law, international organizations and the typical actors. International organizations have initiated a movement towards the adoption of flexible forms of regulation of international relations. They will profoundly change the way in which international law will be created and presented to the recipients of the rule of law. From the very beginning of their activities, organizations preferred a method other than hierarchical command to encourage international cooperation. They will develop a consistent legal technique, aimed at persuading and not compelling their Member States to adopt conduct consistent with the legally binding standard. This article proposes a reflection on soft law and the results of its increasing use in international practices.